Pencegahan Penyalahgunaan Wewenang Pemerintah dalam Membuat Peraturan Perundang-Undangan Sekunder - Aminudin, Cecep (PT. Kaka Media Visi Sistematis, 2025)
The government's authority to make secondary legislation is necessary in a modern state. This article examines the concept of preventing abuse of power in making secondary legislation by the government. The research uses normative legal research methods with secondary data in the form of library materials as basic data which are analyzed qualitatively and presented descriptive-analytically in a statutory and conceptual approach. Based on the results of the study, efforts that can be formulated to prevent abuse of power in making secondary legislation in the context of a democratic welfare state based on the rule of law, consist of aspects related to the process of forming secondary legislation and aspects related to the limits of norms on delegation of authority in primary regulations. Aspects related to the process of forming secondary legislation include public participation and information disclosure, as well as control by the courts, parliament, and the government itself.